2016
DOI: 10.1002/hbm.23404
|View full text |Cite
|
Sign up to set email alerts
|

Depth‐dependence of visual signals in the human superior colliculus at 9.4 T

Abstract: The superior colliculus (SC) is a layered structure located in the midbrain. We exploited the improved spatial resolution and BOLD signal strength available at 9.4 T to investigate the depth profile of visual BOLD responses in the human SC based on distortion-corrected EPI data with a 1 mm isotropic resolution. We used high resolution (350 µm in-plane) anatomical images to determine regions-of-interest of the SC and applied a semi-automated method to segment it into superficial, intermediate, and deep zones. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 51 publications
0
11
1
Order By: Relevance
“…However, several recent high-resolution fMRI studies using millimeter-scale voxels have demonstrated detailed analysis of the functional laminar topography of the human colliculi with reasonable CNR. Indeed, these studies have confirmed the functional properties of the three major layer groups of SC (Katyal & Ress, 2014;Linzenbold & Himmelbach, 2012;Loureiro et al, 2017;Savjani, Katyal, Halfen, Kim, & Ress, 2018;Schneider & Kastner, 2010), as well as the auditory organization of IC (De Martino et al, 2013;Moerel, De Martino, U gurbil, Yacoub, & Formisano, 2015;Ress & Chandrasekaran, 2013), encouraging interest in resolving these laminar variations of human colliculi in more detailed experiments. A recent fMRI study showed depth-dependent variations of the BOLD response with 1-mm sampling in SC (Loureiro et al, 2017).…”
mentioning
confidence: 62%
“…However, several recent high-resolution fMRI studies using millimeter-scale voxels have demonstrated detailed analysis of the functional laminar topography of the human colliculi with reasonable CNR. Indeed, these studies have confirmed the functional properties of the three major layer groups of SC (Katyal & Ress, 2014;Linzenbold & Himmelbach, 2012;Loureiro et al, 2017;Savjani, Katyal, Halfen, Kim, & Ress, 2018;Schneider & Kastner, 2010), as well as the auditory organization of IC (De Martino et al, 2013;Moerel, De Martino, U gurbil, Yacoub, & Formisano, 2015;Ress & Chandrasekaran, 2013), encouraging interest in resolving these laminar variations of human colliculi in more detailed experiments. A recent fMRI study showed depth-dependent variations of the BOLD response with 1-mm sampling in SC (Loureiro et al, 2017).…”
mentioning
confidence: 62%
“…This approach has also been used to demonstrate that the across-subject variability of tonotopic maps in human primary auditory cortex, and the agreement between individual-subject maps and a recent model of the topographic layout, are both improved by removing gradient-echo BOLD voxels sampling the pial surface and considering only those voxels sampled away from these large draining vessels [Ahveninen et al , 2016]. Recent studies have similarly exploited the high-resolution afforded by UHF-fMRI to examine depth-dependent activation profiles and fine-scale functional organization within the hippocampus [Maass et al , 2014] and other subcortical structures [Loureiro et al. , 2017].…”
Section: Fmri Statistical Analyses For High-resolution Data: Intramentioning
confidence: 99%
“…Because of their comparable size and adjacent anatomical location to those of the SC, the IC were selected as control regions to investigate the specificity of SC activity in response to visual stimulus processing. The masks were produced based on anatomical markers that delineate the SC and the IC from surrounding tissue 62 . The medial and posterior boundaries are demarcated respectively by the positions of the PAG 35 and of the cerebral spinal fluid identified on a region of high signal variability (see Fig.…”
Section: Experimental Design and Behavioural Analysismentioning
confidence: 99%